Pre-Sabine Room Acoustic Guidelines on Audience Rake, Stage Acoustics, and Dimension Ratios - Barteld N. J. Postma; Evan Green; Eckhard Kahle; Brian F. G. Katz (Acoustics, 2021)
Prior to Sabine’s work on the Fogg Art Museum and Boston Symphony Hall, several numerical guidelines had been developed and applied to the design of rooms with specific acoustic demands such as theatres, concert halls, and opera houses. Previous papers have discussed guidelines based on the following principles: voice directivity, which was employed in the design of at least 11 rooms; “echo theory”, which quantifies the perception threshold between direct sound and first order reflections in order to prevent echoes from occurring, aiding in the design of at least 7 rooms and leading to the first known use of an acoustic scale model; and notions of reverberation, which influenced the design of at least 14 rooms. This paper discusses three additional pre-Sabine numerical guidelines that were used in room acoustic design: (1) audience rake, (2) stage acoustics and proscenium design, and (3) length, width, and height ratios. The origin of these theories, as well as examples of rooms in which they were applied, are discussed and compared to current practices in room acoustic design.